2015
DOI: 10.1016/j.jcp.2015.04.018
|View full text |Cite
|
Sign up to set email alerts
|

A computationally-efficient, semi-implicit, iterative method for the time-integration of reacting flows with stiff chemistry

Abstract: Please cite this article in press as: B. Savard et al., A computationally-efficient, semi-implicit, iterative method for the time-integration of reacting flows with stiff chemistry, J. Comput. Phys. (2015), http://dx. Abstract A semi-implicit preconditioned iterative method is proposed for the time-integration of the stiff chemistry in simulations of unsteady reacting flows, such as turbulent flames, using detailed chemical kinetic mechanisms. Emphasis is placed on the simultaneous treatment of convection, dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 87 publications
1
50
0
Order By: Relevance
“…39 The chemical source term time integration is performed using a recently developed iterative, semi-implicit method which allows numerical time steps limited here only by the convective Courant-Friedrichs-Lewy (CFL) number, while remaining second order accurate in time and free of lagging errors. 40 The integration uses an approximation of the diagonal of the chemical Jacobian as the preconditioner, which is calculated at negligible computational cost. The overall scheme is second-order accurate in space and time while discretely conserving kinetic energy.…”
Section: B Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…39 The chemical source term time integration is performed using a recently developed iterative, semi-implicit method which allows numerical time steps limited here only by the convective Courant-Friedrichs-Lewy (CFL) number, while remaining second order accurate in time and free of lagging errors. 40 The integration uses an approximation of the diagonal of the chemical Jacobian as the preconditioner, which is calculated at negligible computational cost. The overall scheme is second-order accurate in space and time while discretely conserving kinetic energy.…”
Section: B Governing Equationsmentioning
confidence: 99%
“…41,42 The numerical resolution is designed to resolve all relevant physical length scales of the turbulence and flame, given by considering the criteria κ max η > 1.5 43 and a minimum of 20 grid points per l F . 40 Additional numerical parameters are also provided in Tables I and II. …”
Section: B Governing Equationsmentioning
confidence: 99%
“…34,35 The numerical resolution was selected to resolve all relevant physical length scales of the turbulence and flame, given by the criteria κ max η > 1.5 1 (where κ max is the maximum resolved wavenumber) and a minimum of 20 grid points per l F . 33 The condition κ max η > 1.5 corresponds to recovering 99% of the dissipation, ϵ. 1 Previous work studying the numerical solver, NGA, confirmed that this criterion was sufficient for resolving the velocity field.…”
Section: B Governing Equationsmentioning
confidence: 95%
“…32 The time integration of the chemical source term was performed using a recently developed iterative, semi-implicit method which allows numerical time steps limited here only by the convective Courant-Friedrichs-Lewy (CFL), while remaining second-order accurate in time and free of lagging errors. 33 The overall scheme is second-order accurate in space and time while discretely conserving kinetic energy. 32 Scalar transport was performed with the Bounded QUICK scheme, BQUICK.…”
Section: B Governing Equationsmentioning
confidence: 99%
“…Only a brief overview of the fractional step procedure is given below. More details can be found in [33,34]. An iterative procedure (where the subscript k denotes the iteration number) is used to advance the momentum equations from a time step n to the new time step n + 1 and the scalar equations from a time step n + 1/2 to the new time step n + 3/2.…”
Section: Code Descriptionmentioning
confidence: 99%